NEAR EAST AND AND MIDDLE EAST AS A GEOPOLITICALLY SPLITTED SPACE (modern context) - Vladimir Nikolaevich Ryabtsev; Arushan Arushanovich Vartumyan (Современная наука и инновации, 2022)
In the present article, an analysis of the geopolitical split along the line of confrontation between Iran and Saudi Arabia, Shiism andSunni is carried out. The role of Iran as the first space power in the Islamic world is revealed.